Dunia Manusia-Teknologi Dalam Revolusi Industri Keempat - Thomas Satriya (Arete, 2018)
The Industrial Revolution 4.0 produced a new picture of reality. This happens because humans are helped by technology to perceive all things in more detail, more complex and richer in meaning. This new broader picture forces people to meet new experiences and therefore requires different ways to reflect on the reality of their lives. This paper argues that through its integration with tech¬nology that leads people to recognize and exploit nature in such a way, humans in the industrial revolution 4.0 were brought to an era of natural waste and deprivation. This condition will in turn bring changes to the human way of life that potentially oppress and eliminate some aspects of human life.